Aux confins de la quarantaine : les zombies de notre monde - Veronica Gomez-Temesio (Anthropologie & Santé)
This paper follows the journey of the author when she had to go through a quarantine during the Ebola outbreak that hit Guinea between 2014 and 2015. While she was conducting her fieldwork at the Ebola treatment unit of Wonkifong, Veronica Gomez-Temesio unfortunately broke some biosecurity rules. As she fell ill few days later, she was suspected to have been infected by Ebola and was quarantined as a result. The text tells the story of her experience along with the journey of several patients quarantined in Wonkifong. Through these different stories, the article discusses how the humanitarian politics of triage reveals an inequality of life that is at the core of humanitarian practice. It shows how a personal incident led the author to introduce the concept of zombies in her work.